2012
DOI: 10.1111/j.1600-0897.2012.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of NK Cells in Preeclampsia

Abstract: The regulation of uterine and circulating peripheral blood natural killer (NK) cells has been associated with reproductive immunology such as recurrent pregnancy losses, implantation failures, or preeclampsia. Preeclampsia is a hypertensive disorder of pregnancy characterized by increased blood pressure accompanied by proteinuria and is a major cause of maternal and fetal mortality. Natural cytotoxicity receptors (NCRs) are unique markers, which regulate NK cell cytotoxicity and cytokine production. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 58 publications
3
75
0
3
Order By: Relevance
“…This is because the NK cells to produce Th1 cells that will cause undesirable pregnancy outcome like IUFD (Sharma 2014). A retrospective study by Fukui et al in 2012 also said that NKGA level on NK cells was found increasing in couples with recurrent spontaneous abortion (RSA) and fetal death (Fukui et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the NK cells to produce Th1 cells that will cause undesirable pregnancy outcome like IUFD (Sharma 2014). A retrospective study by Fukui et al in 2012 also said that NKGA level on NK cells was found increasing in couples with recurrent spontaneous abortion (RSA) and fetal death (Fukui et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…NK cells, through CD94/NKG2A receptors, can invade target cells. Uterine NK cells, that can be activated via CD94/NKG2A receptors that can bind HLA-E, have been shown to be associated with immunological processes in IUFD (Mallia et al 2012, Fukui et al 2012. This study aimed to determine the expression of HLA-E and NK cells in trophoblast IUFD that was expected to be a predictor, so that IUFD events may be lowered.…”
Section: Introductionmentioning
confidence: 99%
“…Lower expression of NKp46 may contribute to the type 1 shift of NK cells and may lead to preeclampsia, indicating the potential role of NKp46 in identifying the onset of preeclampsia. 111 …”
Section: Decidual Nk Cells In Uterine Diseasesmentioning
confidence: 99%
“…Preeclampsia occurs in approximately 4% of all pregnancies and is one of the major causes of morbidity and mortality during early pregnancy. 111 Lower expression of vascular endothelial growth factor-C 112 and a lower percentage of Gal-1-expressing NK cells 113 in women are possibly related to preeclampsia. Preeclampsia patients carry abnormal natural cytotoxic receptors on peripheral blood CD56…”
Section: Decidual Nk Cells In Uterine Diseasesmentioning
confidence: 99%
“…31,41,42 In pregnancy pathogenesis, such as preeclampsia, intrauterine growth restriction and pregnancy loss, altered numbers of dNK cells are associated with reduced angiogenesis, defective vascular growth and reduced trophoblast invasion. 45,46 In animal models, Croy and colleagues 47 showed that NK-deficient mice have reduced placental blood supply compared with normal mice. Thus, NK cells are important for a healthy pregnancy outcome.…”
Section: Human Nk Cellsmentioning
confidence: 99%